An Analysis of Students’ Motivation in Learning English at SMAN 8 Kota Jambi Academic Year 2018/2019 - Nurul Dwi Uddiniyah; Efa Silfia (Universitas Batanghari Jambi, 2019)
The purpose of this study was to determine students’ motivation in learning English. This research is one of the influential factors in increasing student learning motivation. Learning success depends on the motivation of high or low students’ in learning. Motivation can encourage students to achieve learning goals in school. The research design in this study is descriptive quantitative survey research. The population of this study was all 11th grade students at SMAN 8 Kota Jambi. The sample used is random sampling. The researcher took students in each 11 IPA class with a total of 15% from each class in taking a sample of 6 people, and from all 11th grades IPA were 48 people as samples. The research instrument was a questionnaire, analysis of data using Likert analysis, percentage formula and to strengthen research, researcher also added interviews. The results of this study are indicated by students' answers in the questionnaire. There are 30 questions in the questionnaire. 15 questions for intrinsic motivation and 15 questions for extrinsic motivation. The calculation shows that students' intrinsic motivation score is 62% and extrinsic students are 38%. This means that students at SMAN 8 Kota Jambi have intrinsic motivation that is higher than extrinsic motivation in learning English.Keywords: English Learning, Motivation.